2017
DOI: 10.4082/kjfm.2017.38.6.346
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Coffee Consumption and Metabolic Syndrome in Korean Adults: Data from the 2013–2014 Korea National Health and Nutrition Examination Survey

Abstract: BackgroundThe gradually increasing demand for coffee worldwide has prompted increased interest in the relationship between coffee and health issues as well as a need for research on metabolic syndrome in adults.MethodsData from 3,321 subjects (1,268 men and 2,053 women) enrolled in the 2013–2014 Korean National Health and Nutrition Examination Survey were analyzed. The subjects were divided into three groups according to their daily coffee consumption. The odds ratios (ORs) and 95% confidence intervals (95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
11
1
1
Order By: Relevance
“…To reduce confounding problems inherent in observational studies, we controlled for dietary intakes of many food groups as well as health behaviours such as smoking and alcohol consumption. Our results were different from those of previous studies which explored the relation of coffee consumption and the metabolic syndrome among Korean adults (13)(14)(15) in that we suggested that moderate coffee consumption of 3-4 times/d was associated with the metabolic syndrome. The differences in results might be due to selection of the study population by rigorous criteria and adjustment for dietary intakes of many food groups in the analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…To reduce confounding problems inherent in observational studies, we controlled for dietary intakes of many food groups as well as health behaviours such as smoking and alcohol consumption. Our results were different from those of previous studies which explored the relation of coffee consumption and the metabolic syndrome among Korean adults (13)(14)(15) in that we suggested that moderate coffee consumption of 3-4 times/d was associated with the metabolic syndrome. The differences in results might be due to selection of the study population by rigorous criteria and adjustment for dietary intakes of many food groups in the analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 12 studies were included in this meta-analysis [4,5,6,7,8,9,10,11,12,13,14,15]. Detailed information on these studies is delineated in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information on these studies is delineated in Table S2. In brief, out of the 12 studies, six studies provided the results for overall adiposity based on BMI [5,6,7,8,11,13] and 10 studies for central adiposity based on WC [4,6,8,9,10,11,12,13,14,15]. By study design, 11 studies were cross-sectional studies and one study was a cohort study [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Kahvenin obezite, nöroplastitite ve nörodejeneratif hastalıklar, kardiyovasküler hastalıklar, metabolik sendrom, antioksidan sistem üzerine olumlu etkileri olduğu gösterilmiştir. 6,8,[16][17][18][19] Bunların yanı sıra, kahve tüketiminden sonra duygusal durumda ve bilişsel performansta iyileşme, uzun süreli egzersiz sırasında dayanıklılıkta gelişme olduğu ifade edilmektedir. 20 Son zamanlarda bağırsak mikrobiyotası ve sağlık üzerine yapılan çalışmaların sayısı artmıştır.…”
Section: Kahve Ve Sağlikunclassified